Construction of Fused Tropone Systems Through Intramolecular Rh(I)-Catalyzed Carbonylative [2+2+2+1] Cycloadditon of Triynes - Teng, Yu-Han G.; Chien, Chih-Wei; Chiou, Wen-Hua; Honda, Tadashi; Ojima, Iwao (Frontiers in Chemistry, 2018)
“Tropone” is a non-benzenoid aromatic skeleton that can be found in a variety of natural products. This cyclohepta-2,4,6-trien-1-one skeleton appears simple, but there have been no straightforward ways to construct this molecular architecture. It is conceivable that this molecule can be constructed via a higher order cycloaddition of three acetylene units and CO, but such process was not known until we have discovered that the carbonylative [2+2+2+1] cycloaddition of triynes can take place in the presence of a Rh complex catalyst and CO. However, this highly challenging process is naturally accompanied by ordinary [2+2+2] cyclotrimization products, i.e., benzenes, as side products. A mechanistic study led to two competing processes wherein the critical CO insertion occurs either to a rhodacyclopentadiene intermediate (Path A) or a rhodacycloheptatriene intermediate (Path B). The DFT analysis of those two pathways disclosed that the Path A should be the one that yields the carbonylative [2+2+2+1] cycloaddition products, i.e., fused tricyclic tropones. A further substrate design, inspired by colchicine structure, led to the almost exclusive formation of a fused tetracyclic tropone from a triyne bearing 1,2-disubstituted benzene moiety in a single step and excellent yield.